2017
DOI: 10.1016/j.cattod.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene CuO/Cu 2 O uniform films inducing MB-degradation under sunlight

Abstract: a b s t r a c tThis study reports on a Cu-sputtered film on polystyrene (PS) leading to the discoloration/degradation of methylene blue (MB) under low intensity solar simulated irradiation. Direct current magnetron sputtering (DCMS) was used to graft uniform, adhesive Cu/Cu oxides on the polystyrene substrate. The kinetics of Cu-PS mediated MB-discoloration adding H 2 O 2 was observed to take place within 90-120 min. The surface potential and pH variation was followed on the Cu-PS surface during MB-discolorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Table 2 also shows that the Cu ions’ release slows down at the end of the recycling (after the 10th cycle) to stabilize at about 2–3 ppb/cycle. These results were slightly similar to previous reports using HiPIMS deposition of Cu x O or TiO 2 /Cu deposited on polyester for photocatalytic applications [31,15,60]. The cumulative ions’ release is still far below the threshold fixed by regulatory bodies for Cu and/or Ti ions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Table 2 also shows that the Cu ions’ release slows down at the end of the recycling (after the 10th cycle) to stabilize at about 2–3 ppb/cycle. These results were slightly similar to previous reports using HiPIMS deposition of Cu x O or TiO 2 /Cu deposited on polyester for photocatalytic applications [31,15,60]. The cumulative ions’ release is still far below the threshold fixed by regulatory bodies for Cu and/or Ti ions.…”
Section: Resultssupporting
confidence: 91%
“…Many studies investigated the effect of (1) semiconductor type such as TiO 2 , ZnO, and SnO 2 [9,10]; (2) the number (mono-, bi-, or tri-doping) and the ratio of doping agents (N, P, Fe, Ag, etc.) [11,12,13,14]; (3) the support type such as polyester, cellulose, polypropylene, or polystyrene [15,16,17]; and (4) the substrate functional groups before the catalyst deposition [18,19]. It had been widely reported that band gap energy, surface area, particles size, and chemical stability were the most important parameters controlling the reactivity of a photocatalytic material [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The stronger adsorption properties of ZnO/Fe 2 O 3 NFs may be ascribed to their higher BET SSA and pore volume. Of especial note, the blank tests (just MB without any catalysts) under UV light reveal negligible photolysis, and only the limited MB can be degraded under UV light irradiation, suggesting the relative stability of MB upon UV light irradiation [43]. However, in the presence of a photocatalyst assisted by UV light illumination, the degradation efficiencies of MB over the photocatalysts are enhanced significantly, which signifies that the degradation of MB in the present study is indeed mainly through a photocatalytic process and/or photocatalysis.…”
Section: Photochemical Performance Evaluationmentioning
confidence: 98%
“…The strong peaks belong to Cu 2 O and CuO, respectively, www.nature.com/scientificreports www.nature.com/scientificreports/ which indicates that Cu is easy to be oxidized with or without UV light irradiation. The presence of shake-up peaks at 945 eV and 963 eV is ascribed to the formation of Cu 2 O [46][47][48][49][50][51] . The XPS results confirm that without the UV irradiation the main surface product on Cu is CuO and it considerably decreases after UV light irradiation.…”
Section: Characterization Of Oxide Filmsmentioning
confidence: 99%